A new paradigm in health systems, 3D technology - Aranda, Monica (2020)
3D technology and its application to biomedical models have generated a new approach to medicine. It will allow producing biomedical devices using patient-specific anatomical data. Since its initial use as pre-surgical visualization models and tool molds, 3D printing has slowly evolved to create devices, implants, unique tissue engineering devices, diagnostic platforms and pharmaceutical management systems. There is a renewed interest in combining stem cells with custom 3D scaffolds for personalized regenerative medicine. And a high potential in the design of personalized tissues and organs, or for the detection of drugs in a specific anatomical structure and a specific biochemical microenvironment for the patient. Achievements in the application of 3D in Medicine are described, and its revolutionary use that will reduce, among others, the time of operations, lower costs of supplies, as well as enabling more precise surgical maneuvers, reducing the risk of bleeding, and infection. At the same time, the advent of 3D printing technologies and personalization perspectives provide important market opportunities, but they also present a serious challenge for public agencies and private entities involved in the different phases of research, control and use of new technologies. Method: In the characterization of the research phenomenon, the descriptive study, the collection of documentary data and the correlation between the different sources were used.